Fairness in the prediction of acute postoperative pain using machine learning models - Davoudi, Anis; Sajdeya, Ruba; Ison, Ron; Hagen, Jennifer; Rashidi, Parisa; Price, Catherine C.; Tighe, Patrick J. (Frontiers in Digital Health, 2023)
Introduction: Overall performance of machine learning-based prediction models is promising; however, their generalizability and fairness must be vigorously investigated to ensure they perform sufficiently well for all patients. Objective: This study aimed to evaluate prediction bias in machine learning models used for predicting acute postoperative pain. Method: We conducted a retrospective review of electronic health records for patients undergoing orthopedic surgery from June 1, 2011, to June 30, 2019, at the University of Florida Health system/Shands Hospital. CatBoost machine learning models were trained for predicting the binary outcome of low (≤4) and high pain (>4). Model biases were assessed against seven protected attributes of age, sex, race, area deprivation index (ADI), speaking language, health literacy, and insurance type. Reweighing of protected attributes was investigated for reducing model bias compared with base models. Fairness metrics of equal opportunity, predictive parity, predictive equality, statistical parity, and overall accuracy equality were examined. Results: The final dataset included 14263 patients (age: 60.72 (16.03) years, 53.87% female, 39.13% low acute postoperative pain). The machine learning model (area under the curve, 0.71) was biased in terms of age, race, ADI, and insurance type, but not in terms of sex, language, and health literacy. Despite promising overall performance in predicting acute postoperative pain, machine learning-based prediction models may be biased with respect to protected attributes. Conclusion: These findings show the need to evaluate fairness in machine learning models involved in perioperative pain before they are implemented as clinical decision support tools.